A Retrospective Study: Quick Scoring of Symptoms to Estimate the Risk of Cardiac Arrest in the Emergency Department. (18th November 2022) - Xu, Yaoke; Zhang, Hua; Zhao, Zongxuan; Wen, Kaifeng; Tian, Ci; Zhai, Qiangrong; Bai, Yi; Li, Shu; Ge, Hongxia; Li, Xiaodan; Zhou, Qidi; Ma, Qingbian
Abstract : Purpose . At present, not enough is known about the symptoms before cardiac arrest. The purpose of this study is to describe the precursor symptoms of cardiac arrest, focusing on the relationship between symptoms and cardiac arrest, and to establish a quick scoring model of symptoms for predicting cardiac arrest. Patients and Methods . A retrospective case-control study was carried out on cardiac arrest patients who visited the emergency department of Peking University Third Hospital from January 2018 to June 2019. Symptoms that occurred or were obviously aggravated within the 14 days before CA were defined as warning symptoms. Results . More than half the cardiac arrest patients experienced warning symptoms within 14 days before cardiac arrest. Dyspnea (p < 0.001 ) was found to be associated with cardiac arrest; syncope and cold sweat are other symptoms that may have particular clinical significance. Gender (p < 0.001 ), age (p < 0.001 ), history of heart failure (p = 0.006 ), chronic kidney disease (p = 0.011 ), and hyperlipidemia (p = 0.004 ) were other factors contributing to our model. Conclusions . Warning symptoms during the 14 days prior to cardiac arrest are common for CA patients. The Quick Scoring Model for Cardiac Arrest (QSM-CA) was developed to help emergency physicians and emergency medical services (EMS) personnel quickly identify patients with a high risk of cardiac arrest.